Pengaruh Media Tiga Dimensi dan Minat Belajar untuk Meningkatkan Hasil Belajar Materi Kenampakan Lingkungan Ditinjau dari Gaya Belajar Siswa Kelas IV SD Negeri 2 Ketanon Tulungagung - Setiawan , Reta Yudi (Neolectura, 2024)
Three-dimensional media is a suitable media used in accordance with the level of development of children aged 7-10 years, a period where children think concretely in accordance with reality. Three-dimensional media can be used in learning so that student interest in learning can increase and have an impact on student learning outcomes. In terms of student learning styles, three-dimensional media can contribute to improving student learning outcomes. The research approach taken is a quantitative research approach using the analysis that will be used to test this hypothesis is path analysis to regularly measure the effect of three-dimensional media and learning interest to improve learning outcomes in terms of student learning styles, especially in understanding the material of Indonesia's natural appearance. Path analysis research is a technique for analyzing the causal relationship that occurs if the independent variable affects the dependent variable not directly, but also indirectly. The results of the study state that: (1) Three-dimensional media has a positive and significant effect on student learning outcomes as evidenced by the sig value of 0.857 which is greater than 0.05 (2) Learning Interest has a positive and significant effect on student learning outcomes as evidenced by the sig value of 0.599 which is greater than 0.05 (3) Three-dimensional media has a positive and significant effect on student learning styles as evidenced by the sig value of 0.082 which is greater than 0.05 (5 ) Learning interests have a positive and significant effect on student learning styles as evidenced by the sig value of 0.206 which is greater than 0.05 (5) Student learning styles can improve learning outcomes as evidenced by the sig value of 0.322 which is greater than 0.05. Keywords: Three-dimensional Media, Learning Interest, Learning Outcomes, Learning Style